Simulasi Antrian Shipping Out pada Gudang Multiguna PT XYZ Untuk Optimalisasi Waktu Tunggu dan Peningkatan Distribusi Menggunakan Software ARENA - Qolbi Rohim, Ahmed; Mega Cattleya PA Islami (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
In the shipping out or delivery service to customers, the loading-unloading process in the warehouse is inevitably linked to queuing. This study discusses how to overcome bottleneck issues during the shipping out process in the warehouse. The research was conducted using a simulation method with ARENA software and queuing theory. The validity test using the Welch Confidence Interval method yielded the result [-26.5714 ≤ μ1 – μ2 ≤ 0.6500], which indicates the data is valid because the value 0 lies within the μ1 – μ2 range. Based on the ARENA output, the Process station to TKBM shows a significantly different utilization rate compared to other workstations, at 0.519160466 or 51.91%. Given this significant difference in availability and performance, an improvement was proposed by adding one more worker for loading-unloading activities. This resulted in a new utilization rate of 0.319951 or 31.99%. This improvement proposal can therefore be considered to reduce queue time.